I am potential eight lessons on living, loving, and reaching your dreams - Hughes, Patrick Henry 1988- (Da Capo Lifelong, 2008)
Patrick Henry Hughes was born with a rare genetic disorder that left him without eyes and physically disabled. But he was also blessed with exceptional musical talent. The inspirational "I Am Potential" recounts the critical lessons he has learned that are at the heart of his success.
Patrick Henry Hughes was born with a rare genetic disorder that left him without eyes and physically disabled. But he was also blessed with exceptional musical talent. The inspirational "I Am Potential" recounts the critical lessons he has learned that are at the heart of his success.
Keywords: Hughes, Patrick Henry -- 1988-; Hughes, Patrick John; Fathers and sons -- Biography; Social adjustment -- Biography; Adjustment (Psychology) -- Biography; Self-actualization (Psychology) -- Biography; Musicians with disabilities -- United States -- Biography; Blind musicians -- United States -- Biography; Musiker; Körperbehinderung; Blindheit; USA; Autobiografie; Erlebnisbericht